2018
DOI: 10.1371/journal.pone.0192618
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining of Streptomyces scabrisporus NF3 reveals symbiotic features including genes related to plant interactions

Abstract: Endophytic bacteria are wide-spread and associated with plant physiological benefits, yet their genomes and secondary metabolites remain largely unidentified. In this study, we explored the genome of the endophyte Streptomyces scabrisporus NF3 for discovery of potential novel molecules as well as genes and metabolites involved in host interactions. The complete genomes of seven Streptomyces and three other more distantly related bacteria were used to define the functional landscape of this unique microbe. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 98 publications
0
8
0
1
Order By: Relevance
“…Many microbes produce siderophore compounds that chelate iron and are then taken up by the microbe. Siderophore production is a common feature of symbionts, including those of plants 97 , where it can facilitate iron acquisition and growth of the host 98,99 . Conversely, this trait is also common in pathogens, in which siderophores are used to sequester iron from the host or other organism 100 .…”
Section: Functional Overview Of the Sponge And Coral Microbiome Profmentioning
confidence: 99%
“…Many microbes produce siderophore compounds that chelate iron and are then taken up by the microbe. Siderophore production is a common feature of symbionts, including those of plants 97 , where it can facilitate iron acquisition and growth of the host 98,99 . Conversely, this trait is also common in pathogens, in which siderophores are used to sequester iron from the host or other organism 100 .…”
Section: Functional Overview Of the Sponge And Coral Microbiome Profmentioning
confidence: 99%
“…In this environment, they are exposed to a permanent state of competition; the production of specific antibiotics may play a decisive role in helping them survive within the rhizosphere microbial community [2]. Among them, it has been revealed that streptomycetes could help to promote the growth of host plants as well as to improve disease symptoms caused by plant pathogens through diverse mechanisms, including the production of bioactive metabolites, which are applied in the direct antagonism against pests and diseases [3,4], in the changes of host physiological function [5], in the induction of host systemic acquired resistances [6], and so on. Among these characteristics, a significant common function for Streptomyces is the antibiotics production [7], which suggests that streptomycetes play a key role in the plant defense and are widely recognized for their potentials in the biocontrol [2].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) created by the plant cells, are generally neutralized by the production of enzymes such as superoxide dismutases (SOD), catalases (CatA), peroxidases (POD), alkyl hydroperoxide reductases (AhpC), genes conferring nitrosative stress caused by reactive nitrogen species, and glutathione-S-transferases (GSTs) in endophytes ( Khare et al, 2018 ). GST was found in the genome of Streptomyces scabrisporus NF3, an endophyte of Amphipterygium adstringens ( Ceapã et al, 2018 ). The ability to alleviate oxidative stress is one attractive property of plant growth promoting bacteria.…”
Section: Discussionmentioning
confidence: 99%